PENYELENGGARAAN MAKANAN BAGI PENDERITA HIPERTENSI DI RUMAH SAKIT UMUM DAERAH PARIAMAN - Sari, Yulia Maya; Baidar, Baidar; Yuliana, Yuliana (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2013)
This study purposetodescribethe implementation offoodin RSUDPariaman.This is a descriptivestudyinvolvinginformantsnutritionist, cook,fooddistributors, and hypertension patients. The results showedthat theimplementation offoodin RSUD Pariamanincludethreestages, that is: 1) planningconsists ofplanningthe menuwith a10dayscycle. Groceryplanning starting fromgrocerypurchasesby pointingthe customerinthe wholesale market.Foodstoragesystem withFIFO, 2)food processing, whichstartsfrom theweighingis donebynutritionist that isrice, side dishes, vegetables, fruitandsalttolow-saltdiettherapypatients.Washingandprocessingtothe presentationfood made​​bycook. The equipment consistsof apreparation tooltypes(prep table, bowl, cutting board, knife, mixer, blender, strainerandmold), processing(stove, frying pan, pot, ladle, woodenspoon), andpresentation(stainlessteel plateandhamperstainlessteel, 3) the presentationanddistribution offoodin hospitalsPariamanusingcentralizedanddecentralizedmanner. Kata Kunci: penyelenggaraan makanan, hipertensi, terapi diet